DISEMINASI TEKNOLOGI DETEKSI KEBUNTINGAN DINI “DEEA GESTDECT” TERHADAP SAPI POTONG DI KINALI KABUPATEN PASAMAN BARAT - Ferry Lismanto Syaiful (Jurnal Hilirisasi IPTEKS, 2018)
The West Pasaman area is an area that has a large enough potential for plantation and agricultural land. Kinali is one of the nagari in Pasaman Barat with an area of 489.64 km₂ is one of the nagari in this Regency which has a large carrying capacity of land and has the potential to develop cattle breeding business. Community service activities are carried out with the aim of providing information to farmers and the public about optimizing the use of "DEEA GestDect" as early pregnancy detection in popular cattle and increasing the knowledge and skills of farmers in livestock reproductive / pregnancy handling in the Kinali Pasaman Barat area. The methods used in this activity are (1) Counseling, and (2) Demonstration of the implementation of Artificial Insemination (IB) and the dissemination of technology using "DEEA GestDect" as a means of early pregnancy detection in popular cattle. From the results of the dedication activities that have been carried out, some conclusions can be drawn as follows: Knowledge and skills of farmers and communities in the Kinali Pasaman Barat area prior to the implementation of this community service are not familiar with early pregnancy detection in cattle. However, the motivation or desire of farmers and the community to undertake cattle breeding business is very large. This can be seen from the desire of farmers and the community to master the technology of early pregnancy detection technology "DEEA Gestdect" on people's cattle is very high. Furthermore, from community service activities can increase the knowledge and skills of the community in early reproductive / pregnancy handling of livestock in the Kinali Pasaman Barat area.